APLIKASI FPE (FAMILY PSYCHOEDUCATION) MOBILE DALAM MENURUNKAN STRES KELUARGA ORANG DENGAN GANGGUAN JIWA - Frastiqa Fahrany; Dedi Kurniawan (STIKes Maharani Malang, 2022)
Introduction: Mental health treatment has moved from hospital-based to community-based psychiatric services. Mental illness often has a 'ripple effect' on families, creating tension, uncertainty, stress, and sometimes significant changes in how people live their lives. The study aims to determine the effect of FPE mobile application to decrease stress level of families living with mental illness. Method: A quasi experiment pre-post test with control group designed apply to this study. A purposive sampling technique carried out in Centered-public health of Bantur. The intervention group with 6 trained cadres give 30 families. Both, pre and posttest measured of stress level. Result and analysis: Pre and posttest measured of stress level. Statistically, a significant mean values difference of stress (p=0.001), as significance as p<0.05. Discussion: Statistically, FPE has a positive effect on the stress level of families living with mental illness. A positive-benefits on the psychological aspect, especially in reducing stress on caregivers for families living with mental illness, but no clinically significant effect on the stress scores of families living with mental illness in relation to high family burdens. Conclusion: FPE has a significance positive effect on the stress level of families living with mental illness, but no clinically significant effect on the stress scores of families living with mental illness. Keyword: Family stress, FPE Mobile, Psychoeducation